Surface Modification of Carbon Nanotubes (Cnnts) as Electrode of Hybrid Energy Storage Device (Supercapacitor) - Mutia Reza; Memik Dian Pusfitasari; Lusi Ernawati; Thalia Winda Sari; Ranti Kusuma Wardhani; Novi Sylvia; Inggit Kresna Maharsih (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
Supercapacitors have an advantage in the form of a higher specific capacitance than conventional capacitors. This alternative is the right idea if it is used to solve the problem of using hybrid energy storage demand. This study aims to analyze the variation in the ratio between activator and carbon nanotubes (Cnnts) that function as electrodes. Electrodes are one of the constituent components of supercapacitors, so they are important to review. Electrodes in the form of Cnnts activated using H2SO4 and HNO3 were analyzed through SEM and FTIR characterization. The activation process produces mesoporous size on the electrode. The activation method is also able to form aromatic compounds that are important for heat stability and electrical conductivity.